81‐3: Reproducing High Dynamic Range Contents Adaptively based on Display Specifications. Issue 1 (2nd June 2017) - Zhu, Ruidong; Sarkar, Abhijit; Emerton, Neil; Large, Tim
Abstract : We developed a new approach to display HDR contents on both HDR and SDR displays. A 12‐bit HDR display is built up to test the algorithm. We have also conducted psychophysical experiments to determine how much dynamic range is needed to make the SDR display resembles the HDR display.